Get Yourself Tested 2011–2012: Findings and prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae at an urban public health system. (April 2015) - Roston, Alicia; Suleta, Katie; Stempinski, Kelly; Keith, Louis; Patel, Ashlesha
During April 2011 and April 2012 the Get Yourself Tested campaign was launched throughout the Cook County Health and Hospitals System to promote testing of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) among 15–25-year-olds in a high-prevalence urban community. Retrospective data were collected and analysed. Demographic differences by CT and GC positivity were evaluated along with factors associated with CT and GC status. A total of 2853 tests were conducted among individuals aged 15–25 years. A total of 2060 (72%) females and 793 (28%) males were tested. Of those tested, 488 (17%) individuals tested positive for either CT or GC or both; 400 (14%) were positive for CT, 139 (5%) were positive for GC. The prevalence for GC was 8.8% ( n = 70) in males compared to 3.3% ( n = 69) in females ( p < 0.001) and the prevalence of CT was 16% ( n = 127) for males compared to 13.3% ( n = 273) for females ( p = 0.057). Women in a high-risk population are more likely to get tested for sexually transmitted infections; however, men are more likely to test positive for CT and GC. Get Yourself Tested is an important campaign to encourage wider spread testing among populations at risk in Cook County.